2021
DOI: 10.15252/embr.202153054
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic resistance to the inhibition of mitochondrial transcription revealed by CRISPR‐Cas9 screen

Abstract: Cancer cells depend on mitochondria to sustain their increased metabolic need and mitochondria therefore constitute possible targets for cancer treatment. We recently developed smallmolecule inhibitors of mitochondrial transcription (IMTs) that selectively impair mitochondrial gene expression. IMTs have potent antitumor properties in vitro and in vivo, without affecting normal tissues. Because therapy-induced resistance is a major constraint to successful cancer therapy, we investigated mechanisms conferring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…To further support our hypothesis, we showed that IMT1, a first-in-class specific and noncompetitive POLRMT inhibitor [ 9 , 30 ], robustly suppressed proliferation (Fig. 3G ) and migration (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…To further support our hypothesis, we showed that IMT1, a first-in-class specific and noncompetitive POLRMT inhibitor [ 9 , 30 ], robustly suppressed proliferation (Fig. 3G ) and migration (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…NSUN2 knocked-out HEK293T cell line [ 149 151 ], YARS2 knocked-out HeLa cell line [ 152 ], and yars2 −/− zebrafish, nsun2 −/− mice [ 150 ] model). At the same time, the CRISPR technique is used in the development of Genomic-Wide Screening Libraries to identify essential genes in different pathways such as oxidative phosphorylation [ 153 ], ATP-modulating [ 154 ], cell death [ 155 ], metabolic resistance [ 156 ], adenine nucleotide translocator—ANT functions [ 157 ], or knock-out screen to identify how mitochondrial stress is relayed to ATF4 [ 158 ].…”
Section: Clinical Applications Of the Crispr Systemmentioning
confidence: 99%
“…Again, exploiting the OXPHOS dependence of cancer cell populations, the inhibition of cell growth was demonstrated in numerous cancer cell lines. Importantly, not all cell lines were responsive to IMTs, and resistance was shown to develop via a loss of genes intrinsic to mammalian target of rapamycin complex 1 (mTORC1) and von Hippel–Lindau (VHL) pathways in addition to an increased expression of mtDNA [155].…”
Section: Mitochondria and Malignancymentioning
confidence: 99%